2012
DOI: 10.1017/s0022377812000311
|View full text |Cite
|
Sign up to set email alerts
|

Laser plasma accelerator driven by a super-Gaussian pulse

Abstract: A laser wakefield accelerator (LWFA) with a weak focusing force is considered to seek improved beam quality in LWFA. We employ super-Gaussian laser pulses to generate the wakefield and study the behavior of the electron beam dynamics and synchrotron radiation arising from the transverse betatron oscillations through analysis and computation. We note that the super-Gaussian wakefields radically reduce the betatron oscillations and make the electron orbits mainly ballistic over a single stage. This feature permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Owing to their larger penetration or propagation in plasma, the super-Gaussian beams are expected to generate nonlinear current in larger region of the plasma and hence, the excitation of THz radiation with very significant and tunable field. This property of these beams will also enhance the interaction length of charged particles with the wakefield [45] excited in a plasma for the particle acceleration [7,46,47]. On the other hand, a little deviation in the super-Gaussian beam profiles with a small dip in the middle of their peak intensity region (generally termed as cosh-Gaussian laser beams) have been used for the second harmonic generation in cold quantum plasma [48] and in ordinary plasma with the relativistic-ponderomotive nonlinearities in the medium [49] due to their better focusing.…”
Section: General Treatment For Super-gaussian Beammentioning
confidence: 99%
“…Owing to their larger penetration or propagation in plasma, the super-Gaussian beams are expected to generate nonlinear current in larger region of the plasma and hence, the excitation of THz radiation with very significant and tunable field. This property of these beams will also enhance the interaction length of charged particles with the wakefield [45] excited in a plasma for the particle acceleration [7,46,47]. On the other hand, a little deviation in the super-Gaussian beam profiles with a small dip in the middle of their peak intensity region (generally termed as cosh-Gaussian laser beams) have been used for the second harmonic generation in cold quantum plasma [48] and in ordinary plasma with the relativistic-ponderomotive nonlinearities in the medium [49] due to their better focusing.…”
Section: General Treatment For Super-gaussian Beammentioning
confidence: 99%
“…Tajima et al [23] have suggested to accelerate electrons toward PeV by LWFA, utilizing a MJ laser (such as the LMJ laser [48]). The conventional RF acceleration may have a difficulty to reach PeV energies, as the synchrotron radiation power loss begins to become formidable beyond 30 TeV [49].…”
Section: B Testing the Relativity In Extreme Energiesmentioning
confidence: 99%
“…The researchers all over the world are putting their efforts to generate the THz radiation sources where the laser plasma interaction has vital role to play. There are a lot of studies on laser plasma interaction, which talk about different mechanisms [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Extremely powerful THz radiations have been achieved by interaction of chirped [24], few cycle laser pulses [25] and tailored laser pulses [26] with plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Extremely powerful THz radiations have been achieved by interaction of chirped [24], few cycle laser pulses [25] and tailored laser pulses [26] with plasmas. In this regard, Villa et al [27] have been able to shape and characterize laser pulses for high gradient accelerators and Ostermayr et al [28] and Malik and co-workers [31,32] have employed super-Gaussian (sG) pulse for laser plasma interaction with regard to their self-focusing effect. We have also made theoretical investigations for the efficient use of super-Gaussian lasers for obtaining THz radiation based on laser beat process [29,34].…”
Section: Introductionmentioning
confidence: 99%